2014
DOI: 10.5935/1678-9741.20140038
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Saphenous Vein Valves and Its Pratical Importance

Abstract: ObjectiveAmong the veins used as a graft in myocardial revascularizations and ends, great saphenous vein is the most used. Knowing the presence and location of valves has great importance when evaluating the surgical anatomy of the great saphenous vein. Despite major surgical application and many works involving great saphenous vein, the number of valves present in it from the saphenous hiatus to the medial epicondyle of the femur is still described inaccurately. The objective of this study is to quantify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…To identify the best portion of the SV as a conduit for bypass surgery, the number and position of valves in the SV were reviewed. A Brazilian study characterized 60 veins from 30 adult cadavers and reported that the average number of valves from the medial epicondyle of the femur to the saphenous hiatus were 4.77 and 4.87 on the left and right sides, respectively 25 . Similarly, a Japanese study of 26 SVs from 20 adult cadavers found 111 valves (average: 4.27) between the SF junction and the upper patellar margin compared to 63 (average: 2.42) valves between the upper patellar margin and the medial malleolus 26 ; they also reported that greatest number of valves were observed within 10 cm from the SF junction and between 35 and 45 cm from the SF junction.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the best portion of the SV as a conduit for bypass surgery, the number and position of valves in the SV were reviewed. A Brazilian study characterized 60 veins from 30 adult cadavers and reported that the average number of valves from the medial epicondyle of the femur to the saphenous hiatus were 4.77 and 4.87 on the left and right sides, respectively 25 . Similarly, a Japanese study of 26 SVs from 20 adult cadavers found 111 valves (average: 4.27) between the SF junction and the upper patellar margin compared to 63 (average: 2.42) valves between the upper patellar margin and the medial malleolus 26 ; they also reported that greatest number of valves were observed within 10 cm from the SF junction and between 35 and 45 cm from the SF junction.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the best portion of the SV as a conduit for bypass surgery, the number and position of valves in SV were reviewed. A Brazilian study characterized 60 veins from 30 adult cadavers and reported that the average number of the valves from the medial epicondyle of the femur to the saphenous hiatus were 4.77 and 4.87 on the left and right side, respectively 23 . Similarly a Japanese study of 26 SV from 20 adult cadavers found 111 valves (average: 4.27) between the SF junction and the upper patellar margin compared to 63 (average: 2.42) valves between the upper patellar margin and the medial malleolus 24 ; they also reported that the valves most valves were observed within 10 cm from the SF junction and between 35-45 cm from the SF junction.…”
Section: Discussionmentioning
confidence: 99%
“…It should be pointed out that hSV has numerous valves irregularly distributed throughout the vein length [ 28 ] . According to Portugal et al [ 29 ] , the average number of valves in hSV (taken from the medial epicondyle of the femur to the saphenous hiatus) is around 4.77-4.87; with a range of two to nine valves being present, all of which were bicuspid. Within hSV valves, at the base of the valve sinus, is located a "bizarre" structure, the agger, comprised mainly of smooth muscle and elastin [ 20 , 30 , 31 ] .…”
Section: Introductionmentioning
confidence: 99%